Membentuk jamaatul muslimin Husein bin Muhsin bin Ali Jabir ; penerjemah, Abu Fahmi ; Rahmat Jenudin ; penyunting, Asri Al-Jufri - HUSEIN BIN MUHSIN ALI JABIR; Abu Fahmi; Jenudin, Rahmat; Al-Jufri, Asri (Gema Insani Press, 1993)
355 hlm. ; 21 cm.